Antibiotic susceptibility and phenotypic profile of species isolated from different clinical samples from health facilities: A cross-sectional study - Khanda Abdulateef Anwar; Shyar Mustafa Saadalla; Aran Jabar Muhammad Amin; Shad Mahdi Ahmed; Mina Kawa Qadir (SAGE Open Medicine)
Background: Staphylococcus species are widely distributed in nature and found in various human body sites. Objectives: To determine the antibiotic susceptibility pattern of Staphylococcus species isolated from different clinical samples. Methods: This cross-sectional study was conducted on 400 clinical specimens from conveniently sampled patients seeking healthcare at two health facilities in sulaimani / Iraq. Bacterial isolation and identification were done using conventional techniques, after which the antibiotic susceptibility profile of Staphylococcus species commonly prescribed antibiotics used in treating infections at the facilities was done using the disc diffusion method. Finally, MecA , methicillin-resistant Staphylococcus aureus and macrolides-lincosamide and streptogramin genes with mupirocin-resistant, beta-lactamase and vancomycin-resistance phenotypes were identified. Results: Staphylococcus aureus was the prevalent isolated species ( n  = 197, 49.3%), followed by Staphylococcus hemolyticus ( n  = 115, 28.8%), Staphylococcus epidermidis ( n  = 49, 12.3%), Staphylococcus hominis ( n  = 9.0, 2.3%), Staphylococcus sciuri ( n  = 8.0, 2.0%) and Staphylococcus lentus ( n  = 4.0, 1.0%). All isolated species resisted Penicillin G, Ampicillin, Cefotaxime and Cefoxitin. Most of the isolates, 89.5% ( n  = 358) had the beta-lactamase phenotype, 18.0% ( n  = 72) had the MecA gene, 2.8% ( n  = 11) the Mupirocin-resistant phenotype, and 2.0% ( n  = 8.0) the vancomycin-resistance phenotype. Additionally, 12 isolates had both methicillin-resistant Staphylococcus aureus (66.7%) and macrolides-lincosamide and streptogramin (65.2%) genes. The majority of the patients, 43% ( n  = 172) were >50 years old and 52.25% ( n  = 209) males. Also, most samples were from patients with urinary tract infection ( n  = 73), wound ( n  = 71), blood ( n  = 35), sputum ( n  = 29), pus ( n  = 28), seminal fluid ( n  = 27), cerebrospinal fluid ( n  = 1.0) and stool ( n  = 1.0). Most isolates that had the MSLb gene were highly significantly resistant to both Clindamycin (94.6%) and Erythromycin (84.7%) ( p  < 0.001). Conclusions: Staphylococcus aureus was the predominant Staphylococcus species isolated from the clinical samples, most of which were resistant to most commonly prescribed antibiotics and had developed resistant genes and phenotypes.